Verifying Linearizability via Optimized Refinement Checking - Liu, Yang; Chen, Wei; Liu, Yanhong A.; Sun, Jun; Zhang, Shao Jie; Dong, Jin Song (IEEE Transactions on Software Engineering, 39(7), July 2013., 2013)
Linearizability is an important correctness criterion for implementations of concurrent objects. Automatic checking of linearizability is challenging because it requires checking that: 1) All executions of concurrent operations are serializable, and 2) the serialized executions are correct with respect to the sequential semantics. In this work, we describe a method to automatically check linearizability based on refinement relations from abstract specifications to concrete implementations. The method does not require that linearization points in the implementations be given, which is often difficult or impossible. However, the method takes advantage of linearization points if they are given. The method is based on refinement checking of finite-state systems specified as concurrent processes with shared variables. To tackle state space explosion, we develop and apply symmetry reduction, dynamic partial order reduction, and a combination of both for refinement checking. We have built the method into the PAT model checker, and used PAT to automatically check a variety of implementations of concurrent objects, including the first algorithm for scalable nonzero indicators. Our system is able to find all known and injected bugs in these implementations.